Molecular evolutionary rates predict both extinction and speciation in temperate angiosperm lineages - Lancaster, Lesley T (BioMed Central, 2010)
BACKGROUND: A positive relationship between diversification (i.e., speciation) and nucleotide substitution rates is commonly reported for angiosperm clades. However, the underlying cause of this relationship is often unknown because multiple intrinsic and extrinsic factors can affect the relationship, and these have confounded previous attempts infer causation. Determining which factor drives this oft-reported correlation can lend insight into the macroevolutionary process. RESULTS: Using a new database of 13 time-calibrated angiosperm phylogenies based on internal transcribed spacer (ITS) sequences, and controlling for extrinsic variables of life history and habitat, I evaluated several potential intrinsic causes of this correlation. Speciation rates (λ) and relative extinction rates (ε) were positively correlated with mean substitution rates, but were uncorrelated with substitution rate heterogeneity. It is unlikely that the positive diversification-substitution correlation is due to accelerated molecular evolution during speciation (e.g., via enhanced selection or drift), because punctuated increases in ITS rate (i.e., greater mean and variation in ITS rate for rapidly speciating clades) were not observed. Instead, fast molecular evolution likely increases speciation rate (via increased mutational variation as a substrate for selection and reproductive isolation) but also increases extinction (via mutational genetic load). CONCLUSIONS: In general, these results predict that clades with higher background substitution rates may undergo successful diversification under new conditions while clades with lower substitution rates may experience decreased extinction during environmental stasis.